Lipedema A Practical Guidebook - Jandali, Zaher; Jiga, Lucian P.; Campisi, Corrado; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is written as a guide for patients suffering from lipedema. Known as a common, painful fat distribution disorder characterised by a disproportional fat accumulation, lipedema represents an unmet medical need where scientific evidence on both pathophysiology and its treatment is still lacking. As the number of affected patients is increasing, besides striving to map the conundrum of clinical signs and relate these to their underlying mechanisms, developing standardised approaches addressing both fat mass reduction and body contouring are key issues able to warrant therapeutic success. In this book, our intention was to look at this complex disease from all its actual perspectives and provide a concise summary of the actual state of knowledge for all those affected. After looking into the most actual data on the aetiology, pathophysiology and course of the disease, the book then focuses on our complex treatment protocols wherecurrent conservative and surgical treatment options are systematically analyzed, considering their long-term chances of success as well as associated risks and side effects. We propose a three step treatment approach. 1st step initiates with weight control and addresses obesity, if present. 2nd step is an individual liposuction therapy plan to treat all lipedema areas, and more. 3rd step includes body contouring surgery, only in patients with massive skin laxity after liposuction and / or massive weight loss. .
Keywords: Surgery, Plastic; Medicine; Dermatology; Surgery; Internal medicine; Plastic Surgery; Clinical Medicine; Dermatology; Surgery; Internal Medicine; Lymphedema -- diagnosis; Lymphedema